Test Evaluation Techniques in Arabic Language Learning: Theory and Practice at SDIT Insan Mulia Pekalongan - Nidhomillah, Abd Rofi Fathoni; Fithtriyah, Aidah; Rosyada, Amrina; Qomari, Nur (Universitas Ahmad Dahlan, 2024)
Arabic language learning at the elementary level is crucial for understanding Islamic values and developing general language skills. Evaluation plays a key role in ensuring effective teaching and learning, especially with the increasing diversity of assessment methods. This study aims to analyze the implementation of Arabic language evaluation at SDIT Insan Mulia Pekalongan, focusing primarily on test evaluation techniques. The research employs a qualitative approach with a case study design, involving interviews, observations, and documentation. The results indicate that evaluations are systematically conducted through various types of tests, including Daily Summative Tests (SH) and End-of-Semester Summative Assessments (ASAS), which assess students' abilities in reading, writing, listening, and speaking. Additionally, oral assessments and memorization practices using songs are implemented to provide constructive feedback. This study also identifies that the use of Item Response Theory (IRT) and Classical Test Theory (CTT) in evaluations can offer a more comprehensive understanding of students' abilities. The findings are expected to contribute to the development of more effective teaching strategies and improve the quality of Arabic language learning at the primary school level.